Phase 2 trial of chewing lignocaine soaked gauze: a novel method to recuse gag reflex - Jasmani, Asraf Haslam; Wan Mokhtar, Wan Muhamad Mokhzani; Che Rahim, Nur Amalina; Mohd. Ridzuan, AS (Surgical Society of Northern Greece, 2020)
Background and aim : The gag reflex has been a hindrance for instrumentation of pharyngeal area. Hence a better method to reduce the gag reflex is investigated. This study aimed to look at the feasibility of chewing lignocaine soaked gauze to reduce gag reflex besides identifying the optimum dosage of lignocaine. Patients and method: This is phase two, 3 arms, double-blinded, randomized control trial where participants were divided into three groups that received either gauze soaked with 160 mg or 320 mg lignocaine or with water base on computer-generated block randomization and were assessed by two assessors at the end of 3 minutes. Result: 30 participants were recruited and divided into three groups with 1:1:1 ratio according to block randomization. Gag reflex reduction was seen highest in group B (M = 2.3, SD = 0.67) and no statistically significant changes in the control group (p = 0.343, 95% CI = -0.126, 0.326). Significant difference in gag reflex score were seen between group A and B with group C (p = 0.000, 95% CI = -2.90, 1.30) and (p = 0.000, 95% CI = -2.70, -1.10) respectively. There was no significant difference between group A and group B (p = 1.00, 95% CI = -1.00, 0.60). No difference were seen in vital signs for all groups during the study. Conclusion: Chewing lignocaine soaked gauze is a feasible method to reduce gag reflex and 320 mg lignocaine is not superior to 160 mg of lignocaine in gag reflex reduction.